(untitled) (Research, Society and Development, 2021)
Companies in Brazil have the need for effective management accounting focused on growth and/or decision making. The general objective of this research was to analyze how Management Accounting can contribute to company decision making. Methodologically, it is a bibliometric analysis through a systematic literature and qualitative review that was developed by bringing together works, such as books, Laws, and published articles. This subject is important because it can cover knowledge in companies with regard to their financial and accounting planning. From the perspective of business management, the process of performance management and assessment and the integration of management information systems for assertive decision-making were observed. It was analyzed that management accounting is an extremely important tool for a well-designed job for a good qualification in decision making, in this way it uses data analysis, cost reduction, financial planning and waste preservation, economic vision. Through the results, the need and importance of using management accounting tools within companies was evident.